Nursing Science Journal of Thailand Index 2020 - Sirorojsakul, Surang; Dechosawang, Siripen; Dacha, Nipaporn (Nursing Science Journal of Thailand, 2020)
Subject Index A Abused teenagers Srijan, P. and Kaesornsamut, P. "Factors correlated with depression among adolescents in foster homes" Nurs Sci J Thail. 2020 ; Jan.-Mar. ; 38(1):86-98. Accidents Yaowares, P. and others. "Influential factors of severity of injury, comorbidity, the number of surgery and the number of complications on hospital length of stay in patients sustaining traumatic injury" Nurs Sci J Thail. 2020 ; Oct.-Dec. ; 38(4):92-103. Aged Prompahakul, R. and others. "The effect of self-regulation program on dietary behavior among older adults with uncontrolled type 2 diabetes" Nurs Sci J Thail. 2020 ; Apr.-Jun. ; 38(2):32-45. Aged--Indonesia Kusuma, M.D.S. and others. "Factors predicting depressive symptoms among older people in community in Bali, Indonesia" Nurs Sci J Thail. 2020 ; Oct.-Dec. ; 38(4):62-76. Albumin Roopngam, T. and others. "Factors predicting cognitive function in patients with sleep-related breathing disorders" Nurs Sci J Thail. 2020 ; Jan.-Mar. ; 38(1):35-46. Antenatal care Nuampa, S. and others. "Experiences of antenatal care attendance and health information seeking among working pregnant women in the large industry plants: descriptive qualitative study" Nurs Sci J Thail. 2020 ; Oct.-Dec. ; 38(4):44-61. Anxiety Lekdamrongkul, P. and others. "The effects of concrete-objective information program on anxiety and functional status among lymphoma patients receiving chemotherapy" Nurs Sci J Thail. 2020 ; Jan.-Mar. ; 38(1):19-34. Petkan, A. and others. "Effect of instructive information with and without the use of pictures on anxiety of women receiving first-time transvaginal/tansrectal ultrasonography" Nurs Sci J Thail. 2020 ; Apr.-Jun. ; 38(2):88-98. Attitude Phoophong, S. and Krainuwat, K. "Predicting factors of intention to quit smoking among employees in public health centers, Bangkok metropolitan administration" Nurs Sci J Thail. 2020 ; Jul.-Sep. ; 38(3):63-77. Phunpom, C. and Phahuwatanakorn, W. "Factors influencing a 6 - month exclusive breastfeeding period in working mothers" Nurs Sci J Thail. 2020 ; 38(1):47-59.